Pure- and mixed-gas permeation properties of highly selective and plasticization resistant hydroxyl-diamine-based 6FDA polyimides for CO2/CH4 separation - Alaslai, Nasser; Ghanem, Bader; Alghunaimi, Fahd; Litwiller, Eric; Pinnau, Ingo (Journal of membrane science, 2016)
The effect of hydroxyl functionalization on the m-phenylene diamine moiety of 6FDA dianhydride-based polyimides was investigated for gas separation applications. Pure-gas permeability coefficients of He, H2, N2, O2, CH4, and CO2 were measured at 35°C and 2atm. The introduction of hydroxyl groups in the diamine moiety of 6FDA-diaminophenol (DAP) and 6FDA-diamino resorcinol (DAR) polyimides tightened the overall polymer structure due to increased charge transfer complex formation compared to unfunctionalized 6FDA-m-phenylene diamine (mPDA). The BET surface areas based on nitrogen adsorption of 6FDA-DAP (54m2g−1) and of 6FDA-DAR (45m2g−1) were ~18% and 32% lower than that of 6FDA-mPDA (66m2g−1). 6FDA-mPDA had a pure-gas CO2 permeability of 14Barrer and CO2/CH4 selectivity of 70. The hydroxyl-functionalized polyimides 6FDA-DAP and 6FDA-DAR exhibited very high pure-gas CO2/CH4 selectivities of 92 and 94 with moderate CO2 permeability of 11 and 8Barrer, respectively. It was demonstrated that hydroxyl-containing polyimide membranes maintained very high CO2/CH4 selectivity (~75 at CO2 partial pressure of 10atm) due to CO2 plasticization resistance when tested under high-pressure mixed-gas conditions. Functionalization with hydroxyl groups may thus be a promising strategy towards attaining highly selective polyimides for economical membrane-based natural gas sweetening. [Display omitted] •Hydroxyl-functionalized 6FDA-DAP and 6FDA-DAR polyimides showed very high pure-gas CO2/CH4 permselectivity of ~90.•Enhanced pure-gas CO2/CH4 permselectivity was primarily due to high diffusivity selectivity.•Mixed-gas selectivity at 10atm partial CO2 pressure was reduced to 75.•Plasticization was minimized by introduction of hydroxyl groups.